Analysis of Melon Growth Due to Application of Silver Black Plastic Mulch and Cow Manure Compost - Ahmad Raksun; Moh Liwa Ilhamdi; I Wayan Merta; I Gde Mertha; Gde Cahyadi Wirajagat (Jurnal Penelitian Pendidikan IPA, 2023)
Melon is a short-lived dicot, that growing up on the ground or on bamboo stakes. Vegetative growth and melon production rate are influenced by internal and external factors. Research has been carried out on the analysis of melon growth due to the application of silver black plastic mulch and cow manure compost in 2023. This study aims to analyze the effect of application of silver black plastic mulch on melon growth; application of cow manure compost on melon growth; interaction of application of silver black plastic mulch and cow manure compost on melon growth. The study was designed in two factors, namely the application of silver black plastic mulch as the first factor and the dosage of cow manure compost as the second factor. The results of the study were: there was an increase in plant height, number of leaves, leaf length and width of melon leaves due to application of silver black plastic mulch; there was an increase in plant height, number of leaves, length of melon leaves due to application of cow manure compost, but the application cow manure compost did not increase the length of melon leaves; there was no increase in all growth parameters measured due to the interaction of silver black plastic mulch and cow manure compost application